2014
DOI: 10.1371/journal.pntd.0002672
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans Binds to Cadherins

Abstract: Leptospirosis, caused by pathogenic species of Leptospira, is the most widespread zoonosis and has emerged as a major public health problem worldwide. The adhesion of pathogenic Leptospira to host cells, and to extracellular matrix (ECM) components, is likely to be necessary for the ability of leptospires to penetrate, disseminate and persist in mammalian host tissues. Previous work demonstrated that pathogenic L. interrogans binds to host cells more efficiently than to ECM. Using two independent screening met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 66 publications
2
63
0
7
Order By: Relevance
“…Although previous works have identified E‐cadherin as a potential ligand of whole Leptospira (Evangelista, Franco, Schwab, & Coburn, ; Evangelista et al, ), this study is the first that identifies a specific leptospiral protein capable of binding this specific human host receptor. Furthermore, we showed that LIC10831‐E‐Cad interactions, while not particularly strong, occur with a K D in the same order of magnitude as the well‐known adhesin InlA, from L. monocytogenes (Lecuit et al, ; Wollert, Pasche, et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…Although previous works have identified E‐cadherin as a potential ligand of whole Leptospira (Evangelista, Franco, Schwab, & Coburn, ; Evangelista et al, ), this study is the first that identifies a specific leptospiral protein capable of binding this specific human host receptor. Furthermore, we showed that LIC10831‐E‐Cad interactions, while not particularly strong, occur with a K D in the same order of magnitude as the well‐known adhesin InlA, from L. monocytogenes (Lecuit et al, ; Wollert, Pasche, et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…Recently, it has been described that Leptospira adheres to vascular endothelium cadherin, 20 which plays an important role in maintaining the vasculature barrier properties. Attachment of Leptospira to the vasculature through cadherin may result in vascular damage, facilitating the escape of the pathogen from the bloodstream into different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, 46 patients were included in the final analysis. All patients were male and between 18 and 24 years old, with a median age of 21 (19)(20)(21)(22)(23) years. No patient had any comorbidity, and all patients had a basal eGFR higher than 80 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…E-cadherin) are utilized by a number of fungal, bacterial and viral pathogens (e.g. Candida albicans, Listeria monocytogenes, Leptospira interrogans and adenovirus) as entry cellular receptors [98100]. In a recent study it has been found that desmoglein-2 (DSG-2), a member of the cadherin protein superfamily and constituent of desmosomes, is the attachment receptor for human species B adenoviruses (Ad3, Ad7, Ad11 and Ad14), which cause respiratory and urinary tract infections [101].…”
Section: Rhinovirus Receptors and Entry To Host Cellsmentioning
confidence: 99%